Analysis of total metals in waste molding and core sands from ferrous and non-ferrous foundries - Miguel, Roberto Esteban (2012)
Waste molding and core sands from the foundry industry have been successfully used around the world as byproducts in geotechnical and agricultural applications. Although waste foundry sands (WFSs) are generally not considered hazardous in nature, relevant data are not available in Argentina. This study aimed to quantify metals in waste molding and core sands from foundries using a variety of metal-binder combinations. Metal concentrations in WFSs were compared to those in virgin silica sands (VSSs), surface soil and soil guidance levels according to hazardous waste law 24.051 from the Argentinean Secretariat of Environment and Sustainable Development. A total analysis for Ag, Al, Ba, Be, Cd, Co, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Pb, Sb, Te, Tl, V, and Zn was conducted on 96 WFSs and 14 VSSs collected from 17 small and medium-sized foundries. The majority of WFSs analyzed, regardless of metal cast and binder type, contained elemental concentrations similar to those found in virgin sands and native soils. In several cases where alkyd urethane binder was used, Co and Pb concentrations were elevated in the waste sands. Elevated Cr, Mo, Ni, and Tl concentrations associated with the virgin sands should not be an issue since these elements are bound within the silica sand matrix. Because of the naturally low elemental concentrations found in most WFSs examined in this study, they should not be considered hazardous waste, thus making them available for encapsulated and unencapsulated beneficial use applications.